Diversity and spatial genetic structure of the common opossum (Didelphis marsupialis) in an urban matrix of Northwestern Colombia (2024)
ABSTRACT: The common opossum (Didelphis marsupialis) is a marsupial widely distributed in the Neotropics, where it lives in urbanized environments. The apparent scarcity and fragmentation of available habitat, and high rates of vehicle collisions, may represent barriers to dispersal. To assess the functional connectivity of this species and its potential use as a model in urban ecology, we evaluated the structure and genetic diversity of opossums in the metropolitan area of the Aburrá Valley (AMVA), Colombia, using sequences of the mitochondrial Cytochrome B (Cytb) gene and nine autosomal microsatellite loci. Although Cytb presented low levels of variation, microsatellite markers revealed high genetic diversity (He = 0.852 and Ho = 0.698). The geographic distribution of mitochondrial lineages and a spatial principal component analysis (sPCA) of microsatellites showed the absence of genetic structure and effective barriers to dispersal of opossums in the study area. This scenario suggests that hostile landscapes such as those in urban environments may be suitable enough to allow the effective connectivity of some species such as the common opossum and others with high dispersal ability in urbanized areas. Nonetheless, it is necessary to evaluate the impact of releases of rescued fauna made by the environmental authority on the population structure of urban opossums.